Respuesta :

Answer:

D.

Step-by-step explanation:

To find the equation of g(x), we can substitute the point into each of the equations.

A. g(x) = (1/4x)^2

1 = (1/4 * 2)^2

1 = (1/2)^2

1 = 1/4

This statement is false, so this is not the equation.

B. g(x) = 1/2 * x^2

1 = 1/2 * (2)^2

1 = 1/2 * 4

1 = 2

This statement is false, so this is not the equation.

C. g(x) = 2x^2

1 = 2 * 2^2

1 = 2 * 4

1 = 8

This statement is false, so this is not the equation.

D. g(x) = (1/2x)^2.

1 = (1/2 * 2)^2

1 = 1^2

1 = 1

This statement is true, so this is your answer.

Hope this helps!

ACCESS MORE
EDU ACCESS
Universidad de Mexico